The Impact of Personality Traits and Intercultural Sensitivities of Nursing Students on Their Professional Values - Dijle Ayar; İlknur Bektaş; Murat Bektaş; Ayşe Arıcıoğlu (Association of Nurse Managers, 2019)
INTRODUCTION: Nurses adopt professional values during their education in order to improve nursing practices and develop their professional identity. Therefore, it is very important to examine the factors that affect the professional values of nursing students. There have been no previous studies evaluating the impact of personal traits and cultural sensitivities of nursing students on their professional values. The aim of the study analyzed the impact of personal traits and cultural sensitivities of undergraduate nursing students on their professional values. METHODS: In order to show the correlations between variables in a more definite way, all undergraduate nursing students (n: 755) who accepted the invitation to participate in this study. The 'Demographic Data Collection Form', 'Personality Test of Adjectives', 'Turkish Intercultural Sensitivity Scale', and 'Nurses' Professional Values Scale' were used to collect study data. The effect of their personal traits on their professional values, intercultural sensitivities were evaluated using linear regression analysis. RESULTS: Examining the relationship between age, gender, school success of undergraduate students, whether they took the course of intercultural nursing and professionalism or not with their professional values, it was found that there was a positive low significant correlation between the age of students and their professional values, there was a positive low significant correlation between the gender of students and their professional values and there was a low significant correlation between school success of students and their professional values. It was found that there was a positive weak significant correlation between personality traits and professional values, and intercultural sensitivities and professional values of nursing undergraduate students. DISCUSSION AND CONCLUSION: It was determined that the mean age, gender, school success, intercultural sensitivity levels and personality traits of nursing students have a positive and significant effect on the professional values of students.